THE PLACE OF CIVIL SOCIETY IDEAS IN OUR NATION-STATEMENT (TAMADDUN NURI JURNALI, 2024)
In this article, the role of the ideas of civil society in Uzbek national statehood and its practical implementation are revealed through examples.